2019
DOI: 10.15376/biores.14.1.1992-2012
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of lignin via Pseudocitrobacter anthropi MP-4 isolated from the gut of wood-feeding termite Microtermes pakistanicus (Isoptera: termitidae)

Abstract: Symbiotic bacteria in the termite gut system may play an important role in lignin degradation that can assist the subsequent saccharification process. Pseudocitrobacter anthropi MP-4, which is capable of degrading lignin components and rapidly growing on various lignin analogue dyes, was successfully screened from the gut of a wood-feeding termite Microtermes pakistanicus. Further decolorization tests with this strain showed that the strain MP-4 potentially produced some relevant extracellular enzymes to parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Bacteria Paenibacillus macerans IIPSP3 isolated from high-level termite Termitidae has produces thermostable xylanase (Dheeran et al 2012), while Pseudocitrobacter anthropic MP-4 from Microtermes pakistanicus showed ligninolytic enzyme activity (Li et al 2019). Three bacteria, namely Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria Paenibacillus macerans IIPSP3 isolated from high-level termite Termitidae has produces thermostable xylanase (Dheeran et al 2012), while Pseudocitrobacter anthropic MP-4 from Microtermes pakistanicus showed ligninolytic enzyme activity (Li et al 2019). Three bacteria, namely Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…These stages were assigned to the residual moisture evaporation. Most decomposition occurred over a wide temperature range from 180 °C to 600 °C (Li, et al, 2019). The treated corn stalk samples had a lower remaining residue (28.8%) at the final temperature than that of the control (30.6%).…”
Section: Effects Of Bio-pretreatment On Thermal Stability Of Crop Str...mentioning
confidence: 93%
“…Some characteristic peaks of lignin were found at 1218 cm −1 . β- O -4 and Cβ disappear [ 40 ] Pseudomonas putida A514 Alkali lignin 1%, – Extent of lignin degradation: 27% [ 41 ] Pseudomonas putida KT3-1 Alkali pretreated lignin (APL) 11.7 g/L, 72 h p -Hydroxybenzoic acid accumulated 20.90% PHA, β- O -4 linkage and small molecule degradation [ 42 ] Pseudomonas putida B6-2 Alkali pretreated lignin (APL) 11.7 g/L, 72 h Extent of vanillic acid degradation: 25.40% (72 h); extent of ferulic acid degradation: 100% (48 h); the molar conversion extent of ferulic acid into vanillic acid was 57.20% Acinetobacter Nocardia autotrophica Nitrated pine lignin –, 20 min Absorbance increases at 430 nm [ 16 ] Acinetobacter PC/4 Nitrated wheat lignin –, 20 min Absorbance increases at 430 nm Acinetobacter sp. ADP1 Alkali pretreatment of lignin 10.5 g/L, 168 h Extent of lignin degradation: 20–25%; absorbance increased at 280 nm [ 22 ] Acinetobacter john­sonii LN2 Alkaline lignin –, 72 h Extent of lignin degradation: 38.80% [ 17 ] Acinetobacter lwoffii LN4 Alkaline lignin –,72 h Extent of lignin degradation: 52% Cupriavidus Cupriavidus necator H16 Alka...…”
Section: Lignin-degrading Bacteriamentioning
confidence: 99%